Question and Answers Forum

All Questions      Topic List

Differentiation Questions

Previous in All Question      Next in All Question      

Previous in Differentiation      Next in Differentiation      

Question Number 165328 by mnjuly1970 last updated on 30/Jan/22

       prove that             Nice   Integral         š›—=āˆ«_0 ^( 1) (( tan^( āˆ’1)  (x^( (3/2)) ))/x^( 2) ) dx  =((Ļ€ + (āˆš3) ln(7 +4(āˆš3) ))/4)             ā–   m.n        āˆ’āˆ’āˆ’āˆ’āˆ’āˆ’āˆ’āˆ’āˆ’

provethatNiceIntegralĻ•=āˆ«01tanāˆ’1(x32)x2dx=Ļ€+3ln(7+43)4ā—¼m.nāˆ’āˆ’āˆ’āˆ’āˆ’āˆ’āˆ’āˆ’āˆ’

Answered by Lordose last updated on 30/Jan/22

Ī¦ = āˆ«_0 ^( 1) ((tan^(āˆ’1) (x^(3/2) ))/x^2 )dx =^(IBP) āˆ’((tan^(āˆ’1) (x^(3/2) ))/x)āˆ£_0 ^1 +(3/2)āˆ«_0 ^( 1) (x^((1/2)āˆ’1) /(1+x^3 ))dx  Ī¦ = āˆ’(š›‘/4) + (3/2)āˆ«_0 ^( 1) (1/( (āˆšx)(1+x^3 )))dx  Ī¦ = āˆ’(š›‘/4) + 3āˆ«_0 ^( 1) (1/((1+x^6 )))dx  Ī¦ = āˆ’(š›‘/4) + 3Ī£_(n=1) ^āˆž (āˆ’1)^(nāˆ’1) āˆ«_0 ^( 1) x^(6nāˆ’6) dx  Ī¦ = āˆ’(š›‘/4) + 3Ī£_(n= 1) ^āˆž (((āˆ’1)^(nāˆ’1) )/(6nāˆ’5))  Ī¦ = āˆ’(š›‘/4) + 3((š›‘/6) + ((coth^(āˆ’1) ((āˆš3)))/( (āˆš3))))  Ī¦ = (š›‘/4) + (āˆš3)coth^(āˆ’1) ((āˆš3))

Ī¦=āˆ«01tanāˆ’1(x32)x2dx=IBPāˆ’tanāˆ’1(x32)xāˆ£01+32āˆ«01x12āˆ’11+x3dxĪ¦=āˆ’Ļ€4+32āˆ«011x(1+x3)dxĪ¦=āˆ’Ļ€4+3āˆ«011(1+x6)dxĪ¦=āˆ’Ļ€4+3āˆ‘āˆžn=1(āˆ’1)nāˆ’1āˆ«01x6nāˆ’6dxĪ¦=āˆ’Ļ€4+3āˆ‘āˆžn=1(āˆ’1)nāˆ’16nāˆ’5Ī¦=āˆ’Ļ€4+3(Ļ€6+cothāˆ’1(3)3)Ī¦=Ļ€4+3cothāˆ’1(3)

Answered by mnjuly1970 last updated on 30/Jan/22

          āˆ’āˆ’āˆ’ solutionāˆ’āˆ’āˆ’        š›—=^(i.b.p)  [((āˆ’1)/x) tan^( āˆ’1)  ( x^( (3/2)) )]_0 ^1 + (3/2) āˆ«_0 ^( 1)  (1/( (āˆšx) .( 1 + x^( 3) ))) dx             = āˆ’(Ļ€/4)  + (3/2) Ī©    where  Ī© = āˆ«_0 ^( 1) (( dx)/( (āˆšx) (1 +x^( 3) )))      Ī© =^((āˆšx) =t)   āˆ«_0 ^( 1) (( 2)/(1 + x^( 6) )) dx =āˆ«_0 ^( 1) (( x^( 4) +1 āˆ’ (x^( 4) āˆ’1 ))/(1+ x^( 6) )) dx           = āˆ«_0 ^( 1) (( (x^( 4) āˆ’x^( 2) +1) + x^( 2) )/(1 + x^( 6) ))dx + āˆ«_0 ^( 1) ((1āˆ’x^( 2) )/(1 āˆ’x^( 2) + x^( 4) )) dx        =   (Ļ€/4) + āˆ«_0 ^( 1) (( 3x^( 2) )/( 1+ (x^( 3) )^( 2) )) dx āˆ’āˆ«_0 ^( 1) ((1āˆ’ x^( āˆ’2) )/(( x + x^( āˆ’1) )^( 2) āˆ’3))dx       = (Ļ€/4)  + (Ļ€/(   4  )) + āˆ«_2 ^( āˆž) (( dx)/(x^( 2) āˆ’3))        = (Ļ€/2)  + āˆ«_2 ^( āˆž)  (dx/(( x āˆ’(āˆš3) )( x +(āˆš3) )))        = (Ļ€/2)  + (1/(2(āˆš3))) { [ln(((xāˆ’(āˆš3))/(x+(āˆš3))) )]_2 ^āˆž }          = (Ļ€/2) + (1/(2(āˆš3))) ln(((2+(āˆš3))/(2āˆ’(āˆš3))) )           = (Ļ€/2) + (1/(2(āˆš3))) ln (7 +4 (āˆš3) )         āˆ“    š›— = (Ļ€/4) + ((āˆš3)/4) ln ( 7 + 4 (āˆš3) )   ā–  m.n

āˆ’āˆ’āˆ’solutionāˆ’āˆ’āˆ’Ļ•=i.b.p[āˆ’1xtanāˆ’1(x32)]01+32āˆ«011x.(1+x3)dx=āˆ’Ļ€4+32Ī©whereĪ©=āˆ«01dxx(1+x3)Ī©=x=tāˆ«0121+x6dx=āˆ«01x4+1āˆ’(x4āˆ’1)1+x6dx=āˆ«01(x4āˆ’x2+1)+x21+x6dx+āˆ«011āˆ’x21āˆ’x2+x4dx=Ļ€4+āˆ«013x21+(x3)2dxāˆ’āˆ«011āˆ’xāˆ’2(x+xāˆ’1)2āˆ’3dx=Ļ€4+Ļ€4+āˆ«2āˆždxx2āˆ’3=Ļ€2+āˆ«2āˆždx(xāˆ’3)(x+3)=Ļ€2+123{[ln(xāˆ’3x+3)]2āˆž}=Ļ€2+123ln(2+32āˆ’3)=Ļ€2+123ln(7+43)āˆ“Ļ•=Ļ€4+34ln(7+43)ā—¼m.n

Answered by Ar Brandon last updated on 30/Jan/22

š›—=āˆ«_0 ^1 ((tan^(āˆ’1) (x^(3/2) ))/x^2 )dx=āˆ’[(1/x)tan^(āˆ’1) (x^(3/2) )]_0 ^1 +(3/2)āˆ«_0 ^1 (x^(āˆ’(1/2)) /(1+x^3 ))dx      =āˆ’(Ļ€/4)+3āˆ«_0 ^1 (dt/(1+t^6 ))=āˆ’(Ļ€/4)+3āˆ«_0 ^1 (dt/((t^2 +1)(t^4 āˆ’t^2 +1)))      =āˆ’(Ļ€/4)+āˆ«_0 ^1 ((1/(t^2 +1))āˆ’((t^2 āˆ’2)/(t^4 āˆ’t^2 +1)))dt=āˆ’(Ļ€/4)+(Ļ€/4)āˆ’āˆ«_0 ^1 ((t^2 āˆ’2)/(t^4 āˆ’t^2 +1))dt      =āˆ’(1/2)āˆ«_0 ^1 ((3(t^2 āˆ’1)āˆ’(t^2 +1))/(t^4 āˆ’t^2 +1))dt=(1/2)āˆ«_0 ^1 ((t^2 +1)/(t^4 āˆ’t^2 +1))dtāˆ’(3/2)āˆ«_0 ^1 ((t^2 āˆ’1)/(t^4 āˆ’t^2 +1))dt      =(1/2)āˆ«_0 ^1 ((1+(1/t^2 ))/((tāˆ’(1/t))^2 +1))dtāˆ’(3/2)āˆ«_0 ^1 ((1āˆ’(1/t^2 ))/((t+(1/t))^2 āˆ’3))dt      =(1/2)[arctan(((t^2 āˆ’1)/t))]_0 ^1 +((āˆš3)/4)[lnāˆ£((t^2 +(āˆš3)t+1)/(t^2 āˆ’(āˆš3)t+1))āˆ£]_0 ^1       =(1/2)((Ļ€/2))+((āˆš3)/4)lnāˆ£((2+(āˆš3))/(2āˆ’(āˆš3)))āˆ£=(Ļ€/4)+((āˆš3)/4)ln(2+(āˆš3))^2       =(Ļ€/4)+((āˆš3)/4)ln(7+4(āˆš3))

Ļ•=āˆ«01tanāˆ’1(x32)x2dx=āˆ’[1xtanāˆ’1(x32)]01+32āˆ«01xāˆ’121+x3dx=āˆ’Ļ€4+3āˆ«01dt1+t6=āˆ’Ļ€4+3āˆ«01dt(t2+1)(t4āˆ’t2+1)=āˆ’Ļ€4+āˆ«01(1t2+1āˆ’t2āˆ’2t4āˆ’t2+1)dt=āˆ’Ļ€4+Ļ€4āˆ’āˆ«01t2āˆ’2t4āˆ’t2+1dt=āˆ’12āˆ«013(t2āˆ’1)āˆ’(t2+1)t4āˆ’t2+1dt=12āˆ«01t2+1t4āˆ’t2+1dtāˆ’32āˆ«01t2āˆ’1t4āˆ’t2+1dt=12āˆ«011+1t2(tāˆ’1t)2+1dtāˆ’32āˆ«011āˆ’1t2(t+1t)2āˆ’3dt=12[arctan(t2āˆ’1t)]01+34[lnāˆ£t2+3t+1t2āˆ’3t+1āˆ£]01=12(Ļ€2)+34lnāˆ£2+32āˆ’3āˆ£=Ļ€4+34ln(2+3)2=Ļ€4+34ln(7+43)

Commented by mnjuly1970 last updated on 31/Jan/22

thanks alot sir brandon

thanksalotsirbrandon

Terms of Service

Privacy Policy

Contact: info@tinkutara.com